Sustainable intensification of cocoa production under a changing climate in Southwest, Nigeria - Kolapo, Adetomiwa; Tijani, Akeem Abiade; Oluwatayo, Isaac Busayo; Ojo, Temitope O.; Khumalo, Nolwazi Z.; Elhindi, Khalid M.; Kassem, Hazem S.; Adeleye, Feyisayo Adeola (Frontiers in Sustainable Food Systems, 2025)
This study examines the sustainable intensification of cocoa production in Southwest Nigeria, focusing on Ondo State, under the pressures of a changing climate. West Africa dominates global cocoa production, with Nigeria ranking as the fourth-largest producer, yet its yields remain low compared to higher outputs in countries like Côte d’Ivoire. Climate change, coupled with low adoption of intensification technologies and extreme weather events, has contributed to declining productivity in Nigeria. This research investigated the determinants and impacts of adopting intensification technologies, such as improved seedlings, fertilizers, and pesticides, on cocoa yields in Ondo State, a major production hub. Using a multi-stage sampling technique, we collected data from smallholder farmers and analyzed with descriptive statistics, a multinomial logit model, and multinomial endogenous switching regression (MESR). Results reveal that farm size, access to credit, membership in associations, age, gender, and positive perceptions significantly influenced technology adoption. The MESR analysis shows substantial yield increases with the adoption of the intensification technologies, notably an 80.62% boost when combining all technologies. The study underscores the potential of sustainable intensification to enhance cocoa productivity and resilience to climate variability, offering policy recommendations including improved credit access, enhanced extension services, and supply chain optimization for inputs. This research bridges climate science and agronomic innovation, providing actionable insights for sustaining Nigeria’s cocoa economy amidst environmental challenges.